Novel mutation and severe respiratory failure in congenital disorders of glycosylation Type Ix - Kılıç, Betül; Akkuş, Nejmiye (The Turkish Journal of Pediatrics, 2020)
Congenital glycosylation disorders (CDG) are a group of rare hereditary metabolic diseases that result from abnormal protein and lipid glycosylation. Virtually all organ systems can be affected, and neurological involvement is particularly severe and disabling. More than 100 CDG types have been reported to date and those numbers are rapidly increasing. Each type is very rare, and the clinical characteristics of each subtype are difficult to determine. There are large numbers of biochemically unresolved cases defined as CDGIx. In this report, we present a 5-year-old boy who had dysmorphic features, hypotonia, developmental and mental delay, epileptic spasms, recurrent apnea and respiratory failure that led to the diagnosis of an unreported mutation of a rare form of CDG-Ix. This mutation in the STT3B gene affects the catalytic subunit of the oligosaccharyltransferase and the recipient substrate properties, which in part have the same functions in N-glycosylation. A novel homozygous mutation in the STT3B presence of c.38C > G that encodes p.S13W (p.Ser13Trp) was detected with next generation sequencing. The CDG clinical spectrum can be unusual, ranging from dysfunction of certain organs to severe multiple system disorders. Respiratory failure has rarely been reported in these cases. Increased types and numbers of patients constitute symptom variety. The identification of new genes and genotype-phenotype relationships may expand the family of CDG.
Keywords: STT3B; congenital disorders of glycosylation Type Ix; novel mutation; respiratory failure